ELECTRO-PHOTONIC EMISSION ANALYSIS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Nevoit, G.V.; Korpan, A.S.; Nastroga, T.V.; Lyulka, N.A.; Sokolyuk, N.L.; Кіtura, O.E.; Potiazhenko, М.М. (World of Medicine and Biology, 2024)
21 polymorbid patients with chronic obstructive pulmonary disease and 85 functionally healthy respondents were obtained by the method of electro-photonic emission analysis. It was found that patients with noncommunicable diseases with chronic obstructive pulmonary disease had significant differences in качественных physical and mathematical parameters of electro-photonic emission analysis, which characterize the shape of the glow compared to functionally healthy young respondents. This testifies to a different course of metabolic processes in them. As the scientific search for adequate and technically simple techniques for use in clinical settings continues, the electro-photonic emission analysis method deserves close attention as a promising candidate for scientific research into the integral level of cellular metabolism/mitochondrial activity. Many questions about the mechanisms of biophotonic communication remain unanswered, so biophotonics of the human body is an important and promising direction for internal medicine and science in general.
Keywords: noncommunicable diseases; chronic obstructive pulmonary disease; electro-photonic emission analysis; biophoton; ultra-weak photon emission